#### Answer

$x = \frac{-3a - b}{a-3}$

#### Work Step by Step

$ax + b = 3x - 3a$
$ax - 3x = -3a - b$
$(a-3)x = -3a - b$
$x = \frac{-3a - b}{a-3}$

Published by
Pearson

ISBN 10:
013421742X

ISBN 13:
978-0-13421-742-0

$x = \frac{-3a - b}{a-3}$

$ax + b = 3x - 3a$
$ax - 3x = -3a - b$
$(a-3)x = -3a - b$
$x = \frac{-3a - b}{a-3}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.